Slidos geomtricos de nuestro entorno - Chue Ignacio, Alex Roberto (2019)
The present work is a model class design of the area of mathematics, entitled "Geometric solids in our environment", aimed at secondary school students who are in the fourth grade. The expected learning of the present design corresponds to the competence of: It solves problems of form, movement and location, whose thematic field is prisms: area, volume and trunk of prism. For the present class design have taken into account the characteristics of logical deductive thinking of the adolescent that make the role of the teacher is a mediator of learning through problematic situations of their environment, the use of concrete material and the use of the technological tools; which make their learning meaningful.